Evaluating transaction costs in the delivery of livestock health services in Kenya - Randolph, Thomas F.; Ndung'u, L.W. (International Society for Veterinary Epidemiology and Economics, 2000)
Although it is widely recognized that non-monetary transaction costs influence the use of livestock health services by smallholder livestock keepers in developing countries, their identification and measurement has remained problematic. This study addresses this gap using a methodology commonly applied in consumer marketing surveys to quantify the relative importance consumers attach to specific characteristics of a product or service.